Browsing the Real World using Organic Electronics, Si‐Chips, and a Human Touch. Issue 10 (7th January 2016) - Berggren, Magnus; Simon, Daniel T.; Nilsson, David; Dyreklev, Peter; Norberg, Petronella; Nordlinder, Staffan; Ersman, Peter Andersson; Gustafsson, Göran; Wikner, J. Jacob; Hederén, Jan; Hentzell, Hans
Abstract : The twinning of the signal‐processing capability of traditional integrated silicon chips with printed organic electronics and sensors is debated and scrutinized, and the use of the human body as a natural local network with the bare hands as the browser of the physical world is discussed. Abstract : Organic electronics have been developed according to an orthodox doctrine advocating "all‐printed'', "all‐organic'' and "ultra‐low‐cost'' primarily targeting various e‐paper applications. In order to harvest from the great opportunities afforded with organic electronics potentially operating as communication and sensor outposts within existing and future complex communication infrastructures, high‐quality computing and communication protocols must be integrated with the organic electronics. Here, we debate and scrutinize the twinning of the signal‐processing capability of traditional integrated silicon chips with organic electronics and sensors, and to use our body as a natural local network with our bare hand as the browser of the physical world. The resulting platform provides a body network, i.e., a personalized web, composed of e‐label sensors, bioelectronics, and mobile devices that together make it possible to monitor and record both our ambience and health‐status parameters, supported by the ubiquitous mobile network and the resources of the "cloud".